2015
DOI: 10.1016/j.compscitech.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization and numerical modeling of damage at the mesoscopic scale of woven polymer matrix composites under quasi-static tensile loading

Abstract: a b s t r a c tThe mechanical behavior of a four-layer plain weave glass fiber/epoxy matrix composite is modeled at the mesoscopic scale, taking into account the dry fabric preforming before resin injection, the relative shift and nesting between fabric layers, and the characteristic damage mechanisms, i.e., intra-yarn cracking and decohesion at the crack tips. The surface strain fields obtained numerically are similar to the strain fields observed at the surface of the specimen. Damage is modeled by introduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…After performing a numerical compaction step, Grail et al [16] developed a nodal distortion algorithm to create matching mesh topologies between orthogonal yarns and investigated the mechanical performance of the resulting composite 40 unit cell. In a subsequent study, Doitrand et al [17] predicted the occurrence of matrix cracks at similar locations to those observed in experiments and studied their impact on the macroscopic mechanical performance.…”
Section: Introductionmentioning
confidence: 88%
“…After performing a numerical compaction step, Grail et al [16] developed a nodal distortion algorithm to create matching mesh topologies between orthogonal yarns and investigated the mechanical performance of the resulting composite 40 unit cell. In a subsequent study, Doitrand et al [17] predicted the occurrence of matrix cracks at similar locations to those observed in experiments and studied their impact on the macroscopic mechanical performance.…”
Section: Introductionmentioning
confidence: 88%
“…Owing to the variability of textile composites, the deformation and failure response are influenced by many factors, such as the reinforcement architecture, the mechanical properties of their constituents and the interaction between the reinforcing fibers and the matrix [4,5]. So far, numerous numerical [6][7][8][9][10] and experimental [5,[10][11][12] studies have been performed in order to examine the mechanical response and failure mechanisms of textile composites under the on-axis mechanical loading. However, such textile laminates are often subjected to local off-axis tensile loading due to its wide application in plane and shell structures.…”
Section: Introductionmentioning
confidence: 99%
“…The unit cell approach is often extended towards damage modelling of woven composites. Examples of such modelling include but not limited to modelling of laminated woven composites under quasi-static tension 2,3 and high strain rate compaction, 4 composites with braided reinforcement 5 and 3D composites. 6 However, the conventional unit cell approach cannot predict variability of the mechanical properties from sample to sample which is usually associated with variability in the intrinsic properties of constituents 7,8 and the geometry of reinforcements such as yarn and layer misalignments 9 arising from textile and composite manufacturing.…”
Section: Introductionmentioning
confidence: 99%